Analisis Kinerja Keuangan Perusahaan yang Melakukan Akuisisi di Bursa Efek Indonesia - Magdalena Nany; Yulianita Pertiwi (Universitas Indraprasta PGRI, 2022)
Acquisitions are considered to be able to create a synergy that leads to an increase in outputs and outcomes from the implementation of the concept of economics of scale. In fact, not all companies experience an increase in performance and several cases state that acquisitions have no effect on financial performance and even reduce the company's financial performance. The purpose of this study was to determine the difference in financial performance before and after acquisitions. Financial performance was proxied by the Current Ratio (CR), Asset Turnover (TATO), Debt to Asset Ratio (DAR), Return On Equity (ROE), and Earnings Per Share (EPS). The research was conducted at the Indonesian Stock Exchange. The object of this research is the company listed on the Indonesia Stock Exchange (IDX) that made the acquisition in 2011-2017. The analysis technique used was Wilcoxon Signed Ranks. Based on the analysis it was found that Total Assets Turnover (TATO) showed differences before and after acquisition. While the Current Ratio (CR) and Debt to Asset Ratio (DAR) showed no differences before and after acquisition. Return On Equity (ROE) showed a difference one year before two years after the acquisition and two years before and two years after the acquisition. Earnings Per Share (EPS) showed a difference only one year before-two years after the acquisition